ANALISIS SEMIOTIK DALAM KONFLIK KELUARGA PADA FILM “ALI & RATU RATU QUEENS” - Adelia Liemansyaputri , Maudy; Muliadi, Muliadi; Majid , Abd (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
Film is one of the mass communication media that can be enjoyed by all circles. Ali & Ratu Ratu Queens is an Indonesian film that has family conflicts that are presented as the core of this film. In this study, the film Ali & Ratu Ratu Queens was analyzed using semiotic analysis according to Charles Sanders Peirce and semiotics according to Roland Barthes. This study uses a qualitative descriptive approach in analyzing the symbols of family conflict according to the semiotics of Charles Sanders Peirce and Roland Barthes. The study lasted for one month by observing film footage. The analysis unit of this study is the film Ali & Ratu Ratu Queens and a collection of cuts of scenes in the film Ali & Ratu Ratu Queens. Using Charles Sanders Peirce's theory of semiotics and Roland Barthes's theory of semiotics. The results showed that the meaning of representations, objects, interpretants, denotations and connotations of the film Ali & Ratu Ratu Queens produced four symbols of family conflict: conflicts between married couples, conflicts between fathers and children, conflicts between mothers and children and conflicts with extended families